Investigation on the ZBG-functionality of phenyl-4-yl-acrylohydroxamic acid derivatives as histone deacetylase inhibitors. Issue 20 (15th October 2015) - Musso, Loana; Cincinelli, Raffaella; Zuco, Valentina; Zunino, Franco; Nurisso, Alessandra; Cuendet, Muriel; Giannini, Giuseppe; Vesci, Loredana; Pisano, Claudio; Dallavalle, Sabrina
Graphical abstract